Aplikasi Perhitungan Biaya Dan Estimasi Waktu Untuk Bangunan Gedung - Ramdani, Ruli Nere; Kartika, Nia; Tahadjuddin, Tahadjuddin (Jurnal Talenta Sipil, 2025)
Cost in construction is located on a cost budget plan document or better known as the RAB. The RAB document provides an overview of the estimated amount of cost for each job by showing the work volume, work cost, materials and workers' needs in completing the project. With that in mind, it will be planned to develop an app for calculating cost and time estimates for each job. In this study used the kind of experimental research, by conducting experimental development of computer applications to carry out calculations of cost and time estimates. The development has produced four main menus, including information, AHSP, RAB, and files. Early development of the application was done using the waterfall method in its development. The final result of this research is an application that has been developed under the name RAB Desktop application can be used in performing cost calculations and estimates of working time with an efficient rate in a fairly significant work time of manual work time. As well as the level of calculation accuracy that yields a difference of -0,000000001% indicates that the application has a density well below the calibration limit.